Treatment-Resistant Major Depression: Rationale for NMDA Receptors as Targets and Nitrous Oxide as Therapy - Zorumski, Charles F.; Nagele, Peter; Mennerick, Steven; Conway, Charles R. (Frontiers in Psychiatry, 2015)
Major depressive disorder (MDD) remains a huge personal and societal encumbrance. Particularly burdensome is a virulent subtype of MDD, treatment resistant major depression (TMRD), which afflicts 15-30% of MDD patients. There has been recent interest in N-methyl-D-aspartate (receptors (NMDARs) as targets for treatment of MDD and perhaps TMRD. To date, most pre-clinical and clinical studies have focused on ketamine, although psychotomimetic and other side effects may limit ketamine’s utility. These considerations prompted a recent promising pilot clinical trial of nitrous oxide, an NMDAR antagonist that acts through a mechanism distinct from that of ketamine, in patients with severe TRMD. In this paper, we review the clinical picture of TRMD as a subtype of MDD, the evolution of ketamine as a fast-acting antidepressant, and clinical and basic science studies supporting the possible use of nitrous oxide as a rapid antidepressant.